2022
DOI: 10.1055/a-1829-9546
|View full text |Cite
|
Sign up to set email alerts
|

Placental Passage of Protopine in an Ex Vivo Human Perfusion System

Abstract: The placental passage of protopine was investigated with a human ex vivo placental perfusion model. The model was first validated with diazepam and citalopram, two compounds known to cross the placental barrier, and antipyrine as a positive control. All compounds were quantified by partially validated U(H)PLC-MS/MS bioanalytical methods. Protopine was transferred from the maternal to the fetal circuit, with a steady-state reached after 90 min. This study compound did not affect placental viability or functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…It is possible that the potential embryonic developmental toxicity of MPTA also affects the levels of estrogen in rats. The results of another study also showed that PRO can be transferred from the mother to the fetal circuit and reach homeostasis through the placental barrier ( Spiess et al, 2022a ). This also provides a partial explanation for the potential embryotoxicity risk of PRO, but the cause of embryotoxicity due to MPTA and its safety for target animals should still be further investigated.…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that the potential embryonic developmental toxicity of MPTA also affects the levels of estrogen in rats. The results of another study also showed that PRO can be transferred from the mother to the fetal circuit and reach homeostasis through the placental barrier ( Spiess et al, 2022a ). This also provides a partial explanation for the potential embryotoxicity risk of PRO, but the cause of embryotoxicity due to MPTA and its safety for target animals should still be further investigated.…”
Section: Discussionmentioning
confidence: 96%